Cognitive Impairment and Evaluation in Psychogenic Nonepileptic Seizures: An Integrated Cognitive-Emotional Approach. (January 2015) - Willment, Kim; Hill, Melanie; Baslet, Gaston; Loring, David W.
Neuropsychological studies comparing patients with psychogenic nonepileptic seizures (PNES) to those with epilepsy have been largely equivocal. The variability in the neuropsychological literature highlights the heterogeneity of the PNES population across a number of psychiatric and neurologic factors. Phenotypic presentations in PNES arise from complex interactions between vulnerable cognitive and emotional systems. We propose that variability in neuropsychological findings in PNES emerge in the context of diverse psychiatric, neurologic, and clinical factors. Traditional assessments that fail to integrate cognitive and emotional/behavioral profiles sufficiently would fall short in characterizing the complexity of brain-behavior relationships in this population. To advance the neuropsychology of PNES, we propose a systematic approach to measure a number of factors that influence cognitive impairment in this population. We begin by reviewing the current neuropsychological literature in PNES and discussing a number of factors that influence cognitive deficits. We then present a comprehensive neuropsychological battery designed to capture elements (cognitive dysfunction, psychopathology, emotion processing deficits) underlying the proposed vulnerable cognitive-emotional system in PNES. It is our hope that the proposed battery will facilitate the aggregation of data across neuropsychological investigations, to allow more advanced statistical analyses, and ultimately enhance our understanding of PNES and the development of effective management and treatment options.